In Operando Atomic Force Microscopy Imaging of Electrochemical Interfaces: A Short Perspective. Issue 24 (19th October 2021) - Neupane, Shova; Valencia-Ramírez, Andrea; Losada-Pérez, Patricia; Renner, Frank Uwe
Abstract : Electrochemical interfaces are at the core of many important current applications, from corrosion and biophysics to electrocatalytic and battery interfaces. Further understanding in the processes taking place at these interfaces is often linked to better observation techniques. In situ or in operando imaging and characterization of the electrochemical interface helps improve our understanding of structural sequences and kinetics of complex processes. Atomic force microscopy (AFM) offers a unique combination to monitor surface morphology and mechanical properties at micro‐ and nanoscale surfaces and solid–electrolyte interfaces. Two examples are given where the application of AFM during electrochemical processes is clearly useful. Organic inhibitors and their behavior play an important role in corrosion mitigation and the influence of thiol monolayers on dealloying is reported: Zinc films find application for coatings or Zn batteries and an in situ electrodeposition study is shortly described. With the ongoing improvement of computational simulations, the broadening of spatiotemporal scales possible with AFM imaging and its combination with mechanical information points in a prospective future for in operando AFM. Abstract : From corrosion to battery interfaces a wide range of electrochemical applications benefit from progress in atomic force microscopy (AFM) and its in operando capability. Two examples of organic corrosion inhibitors and Zn electrodeposition illustrate a short perspective for an even brighter future: the AFM tip still provides plenty of room at the tip.